Postcard from Georg Bredig to Max Bredig, December 20, 1938 - Bredig, Georg (1938)
Georg Bredig (1868-1944) thanks his son, Max Bredig (1902-1977), for correspondence from the United States. He additionally informs Max of increasing discrimination encountered by the family in Germany because of their Jewish heritage. Georg's membership in the Bunsen Society will be terminated at the end of the year and Georg's son-in-law, Viktor Homburger (1888-1968), must liquidate his bank.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Third Reich; Jews, German; Jews, German--Intellectual life; Antisemitism